2019
DOI: 10.1051/epjconf/201922003004
|View full text |Cite
|
Sign up to set email alerts
|

Multistability and high reflectance of a mono-layer of three-level quantum emitters with a doublet in the excited state

Abstract: We study theoretically the nonlinear optical response of a mono-layer of three-level quantum emitters with a doublet in the excited state. It is shown that the layer’s response exhibits multistability. In a certain frequency range, the monolayer operates as a perfect bistable mirror.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The above properties of a V-QE monolayer makes this system promising for various applications in nanophotonics. Preliminary results have been reported in brief communication [19]. It should also be noted that some aspects of unstable behavior of the optical response of a thin layer with a high V-QE concentration have been considered in [20,21].…”
Section: Atoms Molecules Opticsmentioning
confidence: 99%
“…The above properties of a V-QE monolayer makes this system promising for various applications in nanophotonics. Preliminary results have been reported in brief communication [19]. It should also be noted that some aspects of unstable behavior of the optical response of a thin layer with a high V-QE concentration have been considered in [20,21].…”
Section: Atoms Molecules Opticsmentioning
confidence: 99%
“…It has been found that this system can manifest fascinating nonlinear optical effects, including multistability, periodic and aperiodic self-oscillations, chaos, and transient chaos. 2D arrays of V-type quantum emitters reveal similar features [23][24][25][26]. The key ingredient to these nonlinear effects is the secondary field produced by the system dipoles, which provides an intrinsic (mirrorless) positive feedback.…”
Section: Introductionmentioning
confidence: 96%
“…As a result, in addition to bistability, analogous to that manifested by a thin layer of two-level emitters [29][30][31][32][33][34][35][36][37] we predict multistability, self-oscillations and quasichaotic behavior in the optical response of supercrystal of Λ-emitters. Within a certain spectral range, the monolayer operates as a bistable mirror, similar to a 2D supercrystal of SQDs with the ladder and V arrangement of the energy levels [20][21][22]25]. To uncover the character of the instabilities, we use the standard methods of nonlinear dynamics, such as the analysis of the Lyapunov's exponents, bifurcation diagrams, phasespace maps, and Fourier spectra [38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that this system can manifest fascinating nonlinear optical effects, including multistability, periodic and aperiodic self-oscillations, chaos, and transient chaos. 2D arrays of V-type quantum emitters reveal similar features [30][31][32][33]. The underlying characteristic that gives rise to these nonlinear effects is the secondary field produced by the optical transition dipoles, which introduces a mirrorless feedback into the system.…”
Section: Introductionmentioning
confidence: 96%
“…As a result, in addition to bistability, analogous to that manifested by a thin layer of two-level emitters, [36][37][38][39][40][41][42][43][44] we predict multistability, selfoscillations and chaotic behavior in the optical response of the supercrystal of Λ-emitters. Within a certain spectral range, the monolayer operates as a bistable mirror, similar to a 2D supercrystal of SQDs with the ladder and V arrangement of the energy levels [27][28][29]32]. To uncover the character of the instabilities, we use the standard methods of nonlinear dynamics, such as the analysis of the Lyapunov exponents, bifurcation diagrams, phase-space maps, and Fourier spectra [45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%